TREATMENT OF LEACHATE FROM ERBIL LANDFILL SITE BY ELECTRO- AND CHEM-ICAL COAGULATION METHODS - Othman, Mohammed A. (Science Journal of University of Zakho, 2023)
Landfill leachate is commonly heavily contaminated wastewater. and consists of a high number of organic compounds, inorganic salts, toxic gases and heavy metals that exert a serious threat to the environment and public health. Thus, it requires treatments before direct release into receiving waters.  This paper presents the results of electrocoagulation (EC) and chemical coagulation (CC) treatment of leachate from the Erbil landfill site. The removal efficiency of chemical oxygen demand (COD), phosphate (PO43-), total suspended solids (TSS), total organic compound (TOC), and color of leachate was studied using iron and aluminum electrodes. The removal percentages were also compared to those produced by electrochemically generated Fe2+ and Al3+ dosages. The effect of different pH values on the removal efficiency of these parameters was evaluated at optimal conditions. The removal percentages for chemically added coagulants were lower than those for electrochemically generated Fe2+ and Al3+. In EC, the highest COD removal efficiency of 92% and 87% was achieved at the original concentration (C1) for iron and aluminum electrodes, respectively. The iron and aluminum electrodes also showed a maximum color removal of 90% and 95%, respectively, for the original undiluted leachate solution. Both Fe and Al electrocoagulation methods were not effective in removing TOC from the leachate of municipal solid waste. The highest removal efficiency of 78% was achieved at a 1:4 diluted solution (C2) using the Al-electrocoagulation method. The maximum removal percentage for PO43- was 94% at C1 using the Fe-electrocoagulation system. However, both systems were not very effective in removing TSS.
Keywords: landfill leachate; ELS; Electrocoagulation; COD; KEYWORDS: ZigBee, Wireless sensor networks, Simulation results, WSNs Clustering, WSNs Routing protocols, Bluetooth.; TSS